Lateral violence among nurses at a Jamaican hospital : a mixed methods study - Morrison Small, Marilyn; Lindo, Jascinth; Aiken, Joyette; Chin, Claudette (International Journal of Advanced Nursing Studies, 2017)
Purpose: In many first-world settings, lateral violence among nurses is pervasive and has been associated with deleterious psychological effects, high staff turnover and negative patient outcomes. This study explored lateral violence among nurses at a Jamaican hospital.Methods: A fixed concurrent QUAN= QUAL mixed method study design was employed. Data were gathered from 114 registered nurses using the 38-item Brilesâ€™ Sabotage Savvy self-administered questionnaire and two focus group discussions.Results: Exposure to lateral violence was reported by 96% of participants, and 3/4 rated the exposure as moderate to severe. Nurse Managers were the main perpetrators of lateral violence (63%). Lateral violence created a hostile environment, and half of the nurses surveyed indicated an intent to resign. These survey findings were supported by the focus group discussions which yielded themes inclusive of professional disengagement and erosion of team work.Conclusion: The high levels of lateral violence reported in this study indicates an urgent need for the implementation of appropriate workplace violence policies. Reported threats to the healthcare system included poor staff retention and professional disengagement.Highlights:Lateral violence among nurses is one of the most damaging issues affecting the progress of the nursing profession and is well studied in the developed world.The attributes of the phenomenon of lateral violence in a low and middle-income country are described in this paper.Exposure to lateral violence was reported by 96% of participants, forms of lateral violence appeared to be mainly verbal or emotional and nurse managers were the major perpetrators.Assimilated behavior in response to lateral violence among the nurses included professional disengagement, retaliation, avoidance and intent to resign.The pervasiveness of lateral violence among the nurses studied indicates the need to implement appropriate workplace violence policies.Â